Perceived Social Support and Risk of Cyberbullying in Adolescents: A Systematic Review (2022)
This article analyzes the main findings of studies investigating the relationship between perceived social support and cyberbullying in adolescents. We reviewed research papers published between January 2015 and January 2020, included in the Web of Science, Scopus, PUBMED, and Science Direct databases. The protocol was previously registered on the PROSPERO International Systematic Reviews database (CRD42020176938). The article follows the PRISMA guidelines for systematic reviews (Moher et al., 2015). Out of 1929 surveyed articles, 23 met the inclusion criteria and quality standards of scientific evidence set by Downs and Black (1998). Results reveal the types and characteristics of studies and instruments used in assessing social support and cyberbullying and show the relationship between social support and cyberbullying. Keywords adolescents, cyberbullying, perceived social support, qualitative review